The possible role in the ocean heat budget of eddy-induced mixing due to air-sea interaction - Greatbatch, R; Zhai, X; Eden, C; Olbers, D (2007)
The traditional point of view is that in the ocean, the meridional transport of heat is achieved by the wind-driven and meridional overturning circulations. Here we point out the fundamental role played by ocean mixing processes. We argue that mixing (i.e., water mass conversion) associated with eddies, especially in the surface mixed layer, can play an important role in closing the ocean heat budget. Our results argue that the lateral mixing applied at the surface of ocean/ climate models should be playing an important role in the heat balance of these models, indicating the need for physically-based parameterizations to represent this mixing. Copyright 2007 by the American Geophysical Union.